An assessment of the Land Transportation franchising and regulatory Board's (LTFRB) efficiency and effectiveness in the enforcement of the prescribed fare matrix - Ferando, Arlene Barredo; Leda, Lhyni Dignomo (2006.)
The study aimed at assessing the efficiency and effectiveness of the Land Transportation Franchising and Regulatory Board in the implementation of the order with regards to the prescribed fare matrix.
Research Project (Undergraduate, Bachelor of Arts in Political Science-Management) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo.
Keywords: Land Transportation (Philippines)